TEST 33 Examination of Self-Rated Health, Psychological Well-Being and Cardiovascular Health Risks – 10-Year Follow-Up of the Budakalász Epidemiological Study in Hungary - Ehrenberger, Blanka; Ocsovszky, Zsófia; Assabiny, Alexandra; Otohal, József; Papp, Magor; Borenszki-Gutási, Éva; Bagyura, Zsolt; Csabai, Márta (European Journal of Mental Health, 2026)
Introduction: Self-rated health (SRH) predicts morbidity and mortality;however, its long-term trajectories and associations with psychological wellbeing(PWB), health behaviors, and cardiovascular risk remain understudiedin Central and Eastern Europe.Aim: To describe 10-year changes in cardiovascular risk, health behaviors,PWB, and SRH, and to examine how SRH relates to PWB, health behaviors,and cardiovascular risk in a non-clinical Hungarian adult sample.Methods: Adults from Budakalász who participated in a cardiovascularscreening in 2012 were invited to follow up in 2023. The analysis included170 participants aged 45–65 years without major cardiovascular events. SRHwas assessed with a single global item. Anthropometric and laboratory measures,FINDRISK and Framingham risk scores, health behaviors, and a fouritemPWB score derived from the Short Form (36) Health Survey (SF-36)wereincluded. Non-parametric tests, independent sample t-tests, and Spearmancorrelations were applied.Results: Over the 10-year period, SRH showed a modest overall decline,with approximately one-quarter of participants reporting deteriorated SRH,more than half remaining stable, and a minority improving. SRH trajectorieswere not consistently associated with changes in PWB, cardiovascularrisk, or health behaviors. Cross-sectionally, SRH was moderately correlatedwith PWB but only weakly related to health behaviors. Anthropometric dataand cardiovascular risk scores increased, whereas fasting glucose, HbA1c%,and fruit and vegetable consumption improved, and physical activity shiftedtoward lower intensity.Conclusions: SRH was closely aligned with PWB over 10 years but largelydecoupled from objective cardiovascular risk and health behaviors, supportingSRH as a psychologically grounded subjective health construct relevantfor cardiovascular prevention.